Problems of Using a Power of Attorney to Sell in the Transfer of Limited Liability Company Assets (Case Study Decision Number: 472/Pid.B/2023/Pn Tjk) - Abdullah, Ali; Syahpri Kholik (Inovasi Pratama Internasional. Ltd, 2025)
The role of a Notary as a public official is very important and must be able to provide counseling and take the right steps in making authentic deeds by ensuring the formal truth of a legal act, especially a legal act in this case is the transfer of company assets based on a power of attorney to sell and without the approval of the General Meeting of Shareholders. Where the transfer of company assets should refer to the company's articles of association and Law No. 40 of 2007 concerning Limited Liability Companies. The problem raised is the validity of the power of attorney to sell in the transfer of company assets and without the approval of the General Meeting of Shareholders. The research method used is normative legal research, using secondary data consisting of primary, secondary and tertiary legal materials. This study uses a descriptive-analytical data analysis method with a qualitative approach. The results of this study are that if the subjective requirements in making a deed are not met, where the provisions in Article 1320 of the Civil Code must meet the requirements of competence in granting the power of attorney to sell, then the transfer of the asset can be cancelled. A Notary, in carrying out his duties, must be careful, thorough and adhere to the UUJN-UUPJN and KEN.